2010
DOI: 10.1007/s00125-009-1655-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative influence of oxidative stress in the retina of a murine model of diabetes

Abstract: Aims/hypothesisDiabetic retinopathy is a progressive neurodegenerative disease, but the underlying mechanism is still obscure. Here, we focused on oxidative stress in the retina, and analysed its influence on retinal neurodegeneration, using an antioxidant, lutein.MethodsC57BL/6 mice with streptozotocin-induced diabetes were constantly fed either a lutein-supplemented diet or a control diet from the onset of diabetes, and their metabolic data were recorded. In 1-month-diabetic mice, reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
216
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(242 citation statements)
references
References 45 publications
(58 reference statements)
24
216
1
1
Order By: Relevance
“…The sections were examined using a laser confocal microscope as previously described. 29 Vascular leakage and PKC-delta assessment Vascular leakage was assessed by measuring albumin immunofluorescence as previously reported. 26 In addition, in order to further clarify the extra-vascular location of albumin, a double immunostaining for collagen (vascular wall marker) and albumin was performed.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The sections were examined using a laser confocal microscope as previously described. 29 Vascular leakage and PKC-delta assessment Vascular leakage was assessed by measuring albumin immunofluorescence as previously reported. 26 In addition, in order to further clarify the extra-vascular location of albumin, a double immunostaining for collagen (vascular wall marker) and albumin was performed.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Our understanding of the underlying pathogenesis of diabetic retinopathy is becoming increasingly clear, largely due to experiments using animal disease models. Results of these studies have indicated that oxidative stress [6][7][8] and inflammatory signaling [7][8][9][10][11] in the retinal neural tissue are deeply involved in the disease-related mechanisms. A systemic increase in the level of oxidative stress is one of the characteristics of diabetes [12][13][14][15][16][17][18].…”
Section: Neuroinflammatory Signaling and Cellular Disorders In The Rementioning
confidence: 99%
“…A systemic increase in the level of oxidative stress is one of the characteristics of diabetes [12][13][14][15][16][17][18]. In fact, Reactive Oxygen Species (ROS) were found to accumulate in the retinal neurons of a mouse diabetes model, using dihydroethidium (DHE), which reacts with superoxide to generate a fluorescent signal [7]. ROS are usually generated physiologically; however, when their levels exceed the capacity of anti-oxidative enzymes, such as the Superoxide Dismutases (SODs) and catalase, their accumulation leads to dysregulated cellular function.…”
Section: Neuroinflammatory Signaling and Cellular Disorders In The Rementioning
confidence: 99%
See 2 more Smart Citations